Plasma and salivary irisin levels in lepramatous leprosy patients (Annals of Medical Research, 2021)
Aim: We aimed to investigate the plasma and salivary irisin levels in leprosy patients, as well as to evaluate the role of the irisin in the leprosy pathogenesis. Leprosy is a granulomatous disease with the peripheral nerves, mucous membrane, and skin involvement primarily. Irisin, a novel protein, has been associated with several inflammatory diseases and demonstrated in the peripheral nerve cells, deep sebaceous glands, and saliva excessively. To our knowledge, there is no study investigating the irisin levels in patients with leprosy. Material and Methods: We conducted a case-control study on 20 patients with lepromatous leprosy and 20 healthy controls between January 2016 and January 2017. Of the participants, the demographic data and disease history including duration of the disease, any current treatments, and presence of any other family members with leprosy were recorded. The plasma and salivary irisin levels of the participants were measured by enzyme-linked immunosorbent assay (ELISA). Additionally, the serum levels of C-reactive protein (CRP), glucose, hemoglobin A1c (HbA1C), triglyceride, cholesterol, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) were evaluated in both groups.Results: The plasma and salivary irisin levels were significantly lower in the patient group than those in the control group (P = 0.001 and P = 0.03, respectively). In patients with leprosy, the serum and salivary irisin levels had a positive correlation (r: 576, p: 0.008). In addition, there was a negative correlation between the plasma irisin and CRP levels (r: −468, p: 0.037).Conclusion: The irisin may act an immunomodulatory role in leprosy. The irisin production is probably suppressed by the increased inflammatory markers in leprosy or the bacillus to reach the temperature for its reproduction. Further studies are needed to clarify the role and prognostic value of the irisin in leprosy with a large number of patients examined before and after the treatments.
Keywords: Irisin; lepromatous leprosy; saliva